Northern Chemicals Incorporated nicotine sulfate plant - Dacanay, Rolando R. (College of Engineering, 1965)
A proposed plant for the manufacture of nicotine sulfate having an annual capacity of 458,000 liters has been designed for future establishment. This plant is to be located near a river north of the town of San Fernando, La Union. The product obtained from this plant is the aqueous solution containing 40 percent nicotine in the form of nicotine sulfate. The land area necessary for the establishment of this plant is 10,000 square meters with enough space for expansion. The buildings are all one-storey. The total capital investment is P7,577,634.84 of which P3,757,241.36 is the fixed capital investment and P3,820,393.48 are the operational costs. The profit per year before taxes is roughly P7,686,756.52. Pay-off time is estimated to be 0.46 years or approximately six months.